Hubungan Antara Paparan Debu Dengan Gangguan Pernapasan Pekerja Di PT. Semen Bosowa Maros - Nurul Auliya Insani S Nurul; Suharni A. Fachrin; Sitti Patimah (Window of Public Health Journal, 2026)
Exposure to workplace dust is a chemical hazard that can harm workers' health, especially the respiratory system. Fine dust particles can originate from the production process and cause lung dysfunction and even disability. This study aims to determine the relationship between dust exposure and respiratory disorders in workers at PT Semen Bosowa Maros. This study used a quantitative, cross-sectional design. The population in this study was all workers at PT Semen Bosowa Maros, with a sample size of 108 respondents. Data were collected through questionnaires and dust level measurements using a High-Volume Air Sampler. Data analysis was performed using the Spearman correlation test. The results showed that although there was a very weak positive association between dust exposure and respiratory disorders, it was not statistically significant (p = 0.120). Nevertheless, dust exposure remains a risk factor that requires attention. Therefore, companies are advised to continue efforts to prevent and control dust in the workplace. For further research, it is recommended to add additional variables that may influence respiratory disorders and to expand the population coverage to obtain more representative results.